THEORETICAL ASPECT OF SERVICES QUALITY IN SPHERE OF HOSPITALITY - М. V. Arbuzova (Russian Journal of Economics and Law)
Theoretical aspect of services quality as one of the key and actual factors of service increase degree and production efficiency of hotel services, and the development of competitiveness of the enterprises in the sphere of hospitality are considered in the article. The specificity of the contents of services quality is marked. The basic quality performances of services are considered in sphere of hospitality. The basic directions of perfecting of quality system at the enterprises of hospitality are defined in the article.